Outbreak of orally acquired acute Chagas disease in Sucre, 2019-2020 - Villamil-Gómez, Wilmer E. (2022)
Background: In the last two decades, several Latin American countries have experienced multiple outbreaks of oral Chagas disease. The study: Retrospective study analyzing an outbreak of acute oral Chagas disease in Sucre, Colombia during December-January 2020. The cases were confirmed by different diagnostic methods. Finding: During two weeks, 16 cases were confirmed, where the mean age was 14 years and 12 were male. Of the total, 14 patients were hospitalized and 2 died. Clinical manifestations include: fever, facial edema, hepatosplenomegaly, In 13 of the patients Trypanosoma cruzi trypomastigotes were observed in the thin and thick smears. Oral transmission is established as the most likely route in 14 of the patients. Conclusions: Acute orally transmitted Chagas disease can be life-threatening or even fatal, therefore, it is urgent to improve epidemiological control measures at the national level and in other Latin American countries.